Equity in healthcare resource allocation decision making: A systematic review. (February 2017) - Lane, Haylee; Sarkies, Mitchell; Martin, Jennifer; Haines, Terry
Abstract: Objective: To identify elements of endorsed definitions of equity in healthcare and classify domains of these definitions so that policy makers, managers, clinicians, and politicians can form an operational definition of equity that reflects the values and preferences of the society they serve. Design: Systematic review where verbatim text describing explicit and implicit definitions of equity were extracted and subjected to a thematic analysis. Data sources: The full holdings of the AMED, CINAHL plus, OVID Medline, Scopus, PsychInfo and ProQuest (ProQuest Health & Medical Complete, ProQuest Nursing and Allied Health Source, ProQuest Social Science Journals) were individually searched in April 2015. Eligibility criteria for selecting studies: Studies were included if they provided an original, explicit or implicit definition of equity in regards to healthcare resource allocation decision making. Papers that only cited earlier definitions of equity and provided no new information or extensions to this definition were excluded. Results: The search strategy yielded 74 papers appropriate for this review; 60 of these provided an explicit definition of equity, with a further 14 papers discussing implicit elements of equity that the authors endorsed in regards to healthcare resource allocation decision making. Five key themes emerged: i) Equalisation across the health service supply/access/outcome chain, ii) Need or potential to benefit, iii) Groupings of equalisation, iv) Caveats to equalisation, and v) Close enough is good enough. Conclusions: There is great inconsistency in definitions of equity endorsed by different authors. Operational definitions of equity need to be more explicit in addressing these five thematic areas before they can be directly applied to healthcare resource allocation decisions. Highlights: First synthesis of definitions & domains of equity in healthcare resource allocation. Five key themes that are commonly addressed in definitions of equity are discussed. The "Operational Definition of Equity Framework" is proposed. This enables decision makers to construct their own working definition of equity.